Rancang Bangun Aplikasi Market Basket Analysis Untuk Mendukung Persediaan Barang Dengan Algoritma Apriori (Studi Kasus : PT. Mandiri Murni Sejati) - Renaldi; Sholihin (CV. Multi Kreasi Media, 2023)
Inventory of goods is an important thing in a company, store and so on, therefore Inventory can manage the stock of goods in the warehouse to be sold to consumers. PT Mandiri Murni Sejati is a business engaged in the furniture sector, this company requires an inventory information system to help collect more accurate inventory of goods. Therefore, the author tries to make a thesis regarding the inventory stock of goods at PT. Mandiri Pure True that has not been computerized. Data collection of goods stock at PT. Mandiri Murni Sejati still uses a manual system, with a system that is still manual, there is a risk of stockpiling of goods or not synchronizing between data and incoming or outgoing goods. The Design and Build of the Market Basket Analysis application uses the Apriori Algorithm method to run well in accordance with the concepts and designs that have been designed. The purpose of this research is to dig up information and analyze Data Mining and to find out the rules of association of items from the sales transaction data of PT. Mandiri Murni Sejati so as to get more information that can be used for layout decisions and planning for the availability of goods at PT. True Pure Independent. The results of this study indicate that the Market Basket Analysis application with the a priori algorithm method can be used to facilitate the transaction process and the inventory of goods available properly so that it can be used to facilitate the manager or the user. With this inventory information system, it can assist in recording and checking product inventory, and also facilitates sales regarding availability when meeting consumers.